Phytochemistry, Antioxidant and Cytotoxic Activities of Hibiscus (Hibiscus Rosa-Sinensis) Extract on MCF-7 Breast Cancer Cells - Arsianti, Ade; Suhaima, Isma Zahira; Gill, Steven; Fajrin, Ajeng Megawati; Nadapdap, Lince Dameria; Azizah, Norma Nur; Tanimoto, Hiroki; Hirota, Shun (Indonesian Journal of Medical Chemistry and Bioinformatics, 2025)
Background: Breast cancer is the most common type of cancer in women with a very high mortality rate. This cancer is caused by uncontrolled growth of breast cells. Treatments for this malignancy are surgery, chemotherapy, and radiotherapy, however those methods can cause adverse effects and quite expensive. Complementary and alternative medicines (CAMs) are also used to support those main treatments, one of them is herbal medicine. Hibiscus rosa-sinensis is known to have various phytochemical components with antioxidant, antibacterial, anticancer, and analgesic activities. This study is aimed to determine the phytochemical composition, antioxidant activity and cytotoxicity of Hibiscus rosa-sinensis extract towards MCF-7 breast cancer cells. Method: Dried Hibiscus rosa-sinensis was milled to a powder, subsequently extracted by multilevel maceration method using n-hexane, ethyl acetate and ethanol as solvents. Phytochemical components were analyzed by phytochemistry test and thin layer chromatography (TLC). Antioxidant activity was determined using DPPH method, whereas cytotoxic activity towards MCF-7 breast cancer cells was evaluated by MTT assay. Results: Hibiscus rosa-sinensis were proved to contain triterpenoids in all extracts, alkaloids in n-hexane and ethyl acetate extracts, flavonoids and tannins in ethyl acetate and ethanol extracts, and steroids in n-hexane extract. TLC analysis showed n-hexane extract contains 8 phytochemical compounds, ethyl acetate contains 6 compounds, and ethanol extract contains 2 phytochemical compounds. Antioxidant activity of Hibiscus rosa-sinensis extracts towards DPPH free radicals were highly active with IC50 value of 1.56 µg/mL for ethyl acetate extract and 42.30 µg/mL for ethanol extract. Cytotoxicity of ethyl acetate extract of Hibiscus rosa-sinensis towards MCF-7 breast cancer cells was moderately active with IC50 value of 79.37 µg/mL. IC50 value of n-hexane and ethanol extracts were 125.23 µg/mL and 210.77 µg/mL, respectively, in which both were categorized in weakly active. Conclusion: Hibiscus rosa-sinensis contains several phytochemical components which showed highly active antioxidant activity towards DPPH free radicals and moderate-to-weak cytotoxic activity towards MCF-7 breast cancer cells.